Variations in Singapore English a case study based on an excerpt from ’The Teenage Textbook Movie’ - Buang, Sri Norazrin (Journal of Modern Languages, 2017)
Having had its origins from British English, its superstrate language, Singapore English has now evolved to become one of several independent varieties of English; varieties which have been described in various literature as ’New Englishes’ (e.g. Kandiah, 1998, Winford, 2003) as well as ’Non-Native Englishes’ (e.g. Kachru, 1982). As with most other Englishes, Singapore English exists in its standard variety (standard Singapore English) as well as its colloquial variety (colloquial Singapore English). Such variations in Singapore English can be described in terms of two basic frameworks which acknowledge variations on the basis of proficiency or communicative intent as proposed by Platt and Weber’s lectal continuum and Gupta’s diglossia frameworks as well as two other frameworks by Pakir (1995) and Deterding and Poedjosoedamlo (2000) whose frameworks acknowledge and renect variations based on both factors. A brief look into the history of the spread of English in Singapore shows that Singapore English, in its early days, was very much innuenced by the local languages, especially Chinese and Malay. It is understandable, therefore, that the resultant form of Singapore English we have today carries a significant number of features from the local indigenous languages. These features are most prominent in its colloquial form (CSE). Based on a case study of the language used in a Singaporean-made movie, it has been concluded that among the prominent features of CSE in the chosen verbal interaction are the lack of verb innection, lack of subject and the omission of auxilIary verbs. Motivations for the use of such features have also been explored and these include the speaker’s low proficiency level as well as the speaker’s conscious choice to make use ora wider range of resources as a strategic move to create solidarity and mutual understandmg among the interlocutors. It can therefore be concluded that substratal influence plays a very important part in the evolution of the features of Singapore English and that both the Lectal Continuum and Diglossia frameworks (and therefore, especially Pakir’s and Deterding and Poedjosoedarmo’s) reflect these variations in its use.